Doodle Art Therapy to Improve the Quality of Life Vascular Dimensia Prevention - Shindi Hapsari; Umi Hani; Widiyaningsih Widiyaningsih (Global Health Science Group, 2022)
Vascular dementia is a cause of urgent public health problems. Cerebrovascular diseases such as stroke are often the main factor in the incidence of dimensionality. Doodle art as part of the art can be a therapy that provides sensory and cognitive stimulation for sufferers who experience neurological disorders such as brain injuries, strokes, and brain tumors. In this context, therapy is expected to decrease the risk of patients developing vascular dementia, and promote quality of life. This study aimed to evaluate the effectiveness of doodle art therapy on the quality of life in post-stroke patients. This study used quasi-experimental pre and post-test design without control group. The sample of this study was 25 post-stroke community dwelling adult, aged > 25 years, and able to communicate. Respondents participated in doodle art therapy in four session. After the intervention, the quality of life was measured. Univariate statistics were tested to see the respondents’ characteristics and quality of life before and after treatment. The data were normally distributed using the Kolmogorov-Smirnov test. Thus differences in quality of life before and after treatment were analyzed using paired T-Test. After providing the intervention, cognitive function, level of independence and quality of life are tested again and see the difference. We use several tools including a MMSE and WH-QOL brief. Studies show that 87% of respondents are at risk of developing mild dementia, with a moderate quality of life of 60%. 73.5% of respondents were at mild to moderate levels of memory impairment based on MMSE. The quality of life scores was significant difference before and after therapy p value <0.05). Doodle art therapy in nursing interventions is significantly effective for improving the quality of life in the elderly. Doodle art therapy activates the part of the brain that is impaired. The application of doodle art therapy interventions in groups involves group processes in environmental orientation abilities. Doodle art therapy can be a recommendation in efforts to prevent dementia.